Asymmetric Cu(I)-Catalyzed Conjugate Borylation of α,β-Unsaturated Acyl Silanes - Palermo, Anthony F.; Imbriaco, Bianca; Chan, Samantha C.; Doan, Brian A.; Rousseaux, Sophie A. L. (Synlett, 2023)
We report the development of a Cu(I)-catalyzed conjugate borylation of α,β-unsaturated acyl silanes using bis(pinacoloto)diboron. Racemic borylations of β-aryl- and β-alkyl-substituted silyl enones were achieved using ligand-free conditions to access β-borylated acyl silanes in up to 97% yield. Josiphos enabled the synthesis of enantioenriched boronic esters in up to 58% yield and 94% ee. The racemic reaction was demonstrated on 5.0 mmol scale and isolation of the boronic esters was achieved using simple filtration and normal-phase chromatography. This work supplements known methods to access boronic esters from electron-deficient olefins using Cu(I) catalysis.
Keywords: conjugate borylation; α,β-unsaturated acyl silanes; asymmetric borylation; copper catalysis; organoboronic esters